Health-related quality of life in the randomized phase III trial of brigatinib vs crizotinib in advanced ALK inhibitor–naive ALK + non−small cell lung cancer (ALTA-1L). (May 2021) - Garcia Campelo, Maria Rosario; Lin, Huamao M.; Zhu, Yanyan; Pérol, Maurice; Jahanzeb, Mohammad; Popat, Sanjay; Zhang, Pingkuan; Camidge, D. Ross
Highlights: Brigatinib versus crizotinib delayed time to worsening in GHS/QOL in ALK + NSCLC. Time to worsening was also delayed in most function and symptoms scores. Brigatinib improved GHS/QOL and function and symptom scales versus crizotinib. HRQOL was better with first-line brigatinib vs crizotinib in advanced ALK + NSCLC. Abstract: Objective: In ALTA-1 L, first-line brigatinib versus crizotinib significantly prolonged progression-free survival in advanced ALK-positive (ALK+) non–small cell lung cancer (NSCLC). We report health-related quality of life (HRQOL) outcomes from ALTA-1 L. Materials and Methods: HRQOL was assessed using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire–Core 30 (EORTC QLQ-C30) and lung cancer–specific module (QLQ-LC13). HRQOL time to worsening, change from baseline, and duration of improvement were analyzed. Results: EORTC QLQ-C30 and QLQ-LC13 compliance was >90 % for both groups (n = 131 each). Brigatinib versus crizotinib significantly delayed time to worsening in the EORTC QLQ-C30 global health status (GHS)/QOL (median: 26.74 vs 8.31 months; hazard ratio [HR]: 0.70; 95 % CI: 0.49, 1.00; log-rank P = 0.0485); emotional functioning, social functioning, fatigue, nausea and vomiting, appetite loss, and constipation scales (log-rank P < 0.05); delays in time to worsening for the physical, role, and cognitive functioning scales were not statistically significant. Mean change from baseline showed greater improvement in GHS/QOL and most EORTC QLQ-C30 functional and symptom scales with brigatinib versus crizotinib. Among patients with GHS/QOL improvement, brigatinib had longer duration of improvement versus crizotinib (median: not reached vs 11.99 months); similar results were seen in the physical, role, emotional, and social functioning; fatigue; nausea and vomiting; and appetite loss scales. Median time to worsening in dyspnea (QLQ-LC13) was 23.98 versus 8.25 months (brigatinib vs crizotinib; HR: 0.64; 95 % CI: 0.39, 1.05). Conclusion: Brigatinib significantly delayed time to worsening and prolonged duration of improvement in GHS/QOL versus crizotinib, supported by improvement in functional and symptom scores. These preliminary analyses suggest brigatinib is the first ALK inhibitor with better HRQOL versus another ALK inhibitor in ALK inhibitor–naive advanced ALK + NSCLC.